Determination and analysis of basic physical and contact mechanics parameters of quinoa seeds by DEM - Shi, Linrong; Zhao, Wuyun; Sun, Bugong; Sun, Wei; Zhou, Gang (International Journal of Agricultural and Biological Engineering, 2023)
Quinoa is an ancient crop that is nutritious, balanced, and suitable for most people. However, it has not been known and sought by the public until modern times. In recent years, quinoa has been intensively known and widely grown in China. Quinoa mechanized production machines have also been developed. With the help of DEM, we design and optimize the quinoa combined seeder, improving seeding efficiency and quality. In this paper, the basic physical and contact mechanics parameters required for the Hertz-Mindlin (no slip) of quinoa seeds in EDEM software were determined. The coefficient of rolling friction of quinoa seeds was calibrated on DEM, and which of Long Quinoa 4 is 0.043, and that of Meng Quinoa 4 was 0.016. Meanwhile, we can find that the coefficient of rolling friction strengthens the shape to restrict rolling and weakens the shape to increase rolling. The above research provides simulation parameters for the design and optimization of quinoa seed seeding machinery.Keywords: quinoa seeds, physical parameters, contact parameters, calibration, DEMDOI: 10.25165/j.ijabe.20231605.7837Citation: Shi L R, Zhao W Y, Sun B G, Sun W, Zhou G. Determination and analysis of basic physical and contact mechanics parameters of quinoa seeds by DEM. Int J Agric & Biol Eng, 2023; 16(5): 35–43.